Addressing Challenges in Recruiting Diverse Populations for Research: Practical Experience From a P20 Center - Wright, Fay; Malone, Susan Kohl; Wong, Agnes; D'Eramo Melkus, Gail; Dickson, Victoria Vaughan (Nursing research (New York), 2022)
Improving the recruitment and retention of underrepresented groups in all research areas is essential for health equity. However, achieving and retaining diverse samples is challenging. Barriers to recruitment and retention of diverse participants include socioeconomic and cultural factors and practical challenges (e.g., time and travel commitments). The purpose of this article is to describe the successful recruitment and retention strategies used by two related studies within a P20 center funded by the National Institute of Nursing Research focused on precision health research in diverse populations with multiple chronic conditions, including metabolic syndrome. To address the complexity, biodiversity, and effect of metabolic syndrome and multiple chronic conditions, we developed culturally appropriate, multipronged recruitment and retention strategies for a pilot intervention study and a longitudinal observational pilot study within our P20 center. The following are the underlying principles that guided the recruitment and retention strategies: (a) flexibility, (b) active listening and bidirectional conversations, and (c) innovative problem solving. The intervention study (Pilot 1) enrolled 49 participants. The longitudinal observational study (Pilot 2) enrolled 45 participants. Women and racial/ethnic minorities were significantly represented in both. In Pilot 1, most of the participants completed the intervention and all phases of data collection. In Pilot 2, most participants completed all phases of data collection and chose to provide biorepository specimens. We developed a recruitment and retention plan building on standard strategies for a general medical population. Our real-world experiences informed the adaption of these strategies to facilitate the participation of individuals who often do not participate in research-specifically, women and racial/ethnic populations. Our experience across two pilot studies suggests that recruiting diverse populations should build flexibility in the research plan at the outset.